Changing Theory and Practice? CAA and Archaeology's Digital Turn. - Huggett, Jeremy (Journal of Computer Applications in Archaeology, 2024)
Over the past sixty years, digital archaeology has become a major research area equipped with its own international conferences and journals. During that period, the practical uses of computer techniques and technologies and the computations that can be applied in archaeological analysis have been explored, and digital tools, digital infrastructures, and digital methodologies have been studied along with their implementation into mainstream archaeological practice. At face value, therefore, digital archaeology has been truly transformative over the period. As the Computer Applications and Quantitative Methods (CAA) community passes 50 years of annual meetings and proceedings, it is an appropriate time to take stock of the contribution that CAA has made to the role of digital archaeology across the discipline more generally. This paper uses a citation analysis to investigate when and where CAA publications are cited by the broader archaeological community, and in doing so critically assesses the history of CAA and its contribution to archaeology's digital turn.